Survey Leading Organization Pada Organisasi Islam - Dian J. Bantam (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
Islamic University is islamic organization that care with public's need, especially for education. One of the vision of Islamic Universities is leading and islamic, to bravely innovate and develop education based on islam. The aim of this study examined one models of Four God-Guided Organizations, there are leading organization. Sample included Islamic universities in Yogyakarta with 112 employees. MANOVA and descriptive test is used to analyze the data. Results showed approximately 48% of Islamic organizations including very low category and 6.3% very high category. In addition, results showed significant differences in the important component of leading organization (F (df22, 89) = 3.55, p < 0.05). Behavior aspects are very effective in Islamic organizations (M=11.44, SD=1.55) and last aspect are products (M=5.58, SD=1.01).Keyword: Four God-Guided Organizations (FGGO), Leading Organization (LO), Organisation Innovativeness, Survey.